ANALISIS HISTORIS TERHADAP MISI GEREJA MULA-MULA DAN PENGARUHNYA BAGI PERTUMBUHAN GEREJA MASA KINI - Naftalia Patrisya; Mexwindi Mexin Kananlua’ (JOURNAL OF COMMUNITY DEDICATION, 2023)
The early church is the main image of the church and the real protector of the church that is now well in the midst of world life, even in the context of the Indonesian nation. It should also be understood that the early Church made a very big contribution to the existence of the church today. However, one thing is certain that a great contribution to the presence of the church today does not just appear out of nowhere. The early church certainly did various things to expand its reach so that all corners of the world could get the good news or the Gospel of God. For this reason, in this paper, the author will examine how the early Church's mission was to expand and spread the teachings of Christianity in the perspective of historical analysis. In this article we will see how the early Church carried out the great commission of Jesus Christ contained in Matthew 28:19-20 and we will see how the impact of the early Church's missionary ministry has on the church today.